Could we rely on market discipline as a substitute for insurance regulation? - Castagnolo, Fernando (2013)
Purpose: The purpose of this paper is to examine empirically whether the market discipline works, and if so, whether it is a complement or substitute of prudential regulation in the insurance markets. Market discipline is intended as “the power of … market forces … to evaluate and control the risky behaviour of the financial institutions”. The authors' formal hypothesis is that if market discipline works as complementary to prudential regulation, the response of the insured is expected to be weaker than if market discipline acts as a substitute to prudential regulation. Design/methodology/approach: The authors designed an experiment examining policy subscription reaction to adjustments in insurers' risk ratings in three different regulatory environments, to compare market discipline in each market. An econometric model was estimated to test the reaction of policy subscription to changes in credit ratings of the insurers. Findings: The findings indicate that more market discipline was exerted in the crisis period, and more intensely where it is intended to replace regulation. A formal hypothesis was tested: in a less regulated environment, consumers' protection rests more heavily on their caution and use of market information about the insurers' financial condition. Research limitations/implications: The research is constrained by the availability and detail of the publicly available data. Practical implications: The results imply that regulation and market discipline work more as complements than as substitutes. Social implications: Market discipline does not replace prudential regulation in the insurance market. Originality/value: The approach presented in the paper adds to precedent work studying comparatively different regulatory environments, and also concerns the response of market discipline in the financial crisis context.